The Current Experiences of Physical Education Teachers at Schools for Blind Students in the United States. (September 2016) - Haegele, Justin A.; Lieberman, Lauren J.
Introduction: It has been well established that children with visual impairments tend to be less physically active and more delayed in motor skills than their sighted peers. As a result, there has been some research focusing on inclusive physical education for these children. However, there is a clear lack of research on the current status of physical education for children in residential schools. Purpose: The purpose of this study was to gain insight into the current experiences of physical education teachers at schools for blind students in the United States. Methods: A questionnaire was sent to 51 physical education teachers from 35 schools for blind students across the country. Data from closed-ended and short-response open-ended questions were analyzed descriptively, using frequencies and percentages, across four main areas: teacher characteristics, teaching practices, student populations, and facilities. Results: Most physical education teachers reported that their schools employ certified physical educators, use curricula that are tied to state or national standards, possess a variety of facilities for their students to use in physical education, offer a variety of sports (with the most common being wrestling), and teach a varied population of students. Discussion: A number of findings emerged from this study. Positive findings include: schools are hiring teachers who are certified in physical education or adapted physical education; they are utilizing curricula that are tied to their state and national standards; and they are offering a variety of sports after school. The few factors of concern are: the lack of validated assessments in the field of adapted physical education and, therefore, the limited use of validated assessments; and the need for additional training for teachers related to children who are deafblind and students with both visual impairments and autism spectrum disorder.